3. The effect of environmental enrichment on GBL-induced Infantile Spasm-like seizures in Ts65Dn mice. Issue 8 (August 2018) - Li, Chun Kit; Scott, Brian W.; Cortez, Miguel A.
Abstract : Infantile spasms (IS) is the most common and severe form of epilepsy that occurs in infants between four and twelve months of age. Symptoms of IS include sporadic flexion and/or extension in all limbs and torso, multifocal spike discharges and manifestation of cognitive and psychomotor impairments later on in development. A strong correlation between Down Syndrome (DS) and IS was reported in recent research. It has also been shown that environmental enrichment was able to reduce the severity of atypical absence epilepsy, which is observed after IS in some patients, in a rat model. We therefore used the Down Syndrome mouse model (Ts65Dn) to test the hypothesis that environmental enrichment would reduce the number of γ -butyrolactone (GBL)-induced spasms in Ts65Dn mice. There was a significant decrease in the number of four-limb extensions 10-min-post-injection in Ts65Dn mice housed in an enriched environment compared to those in standard caging. The effect of environmental enrichment was non-significant 20- and 30-min-post-injection. The number of four-limb extensions, however, was significantly reduced at all three time points in the control mice in enriched housing relative to standard condition. Here, we also report GBL-induced flexion phenotypes that were not seen in previous studies using the Ts65Dn model. Our results suggest that the protective effects of environmental enrichment might only be applicable to non-DS infants. It also provides a potential model to study for the mechanism behind IS flexions in the future.